PENGARUH TABUNGAN DAN DEPOSITO TERHADAP PENYALURAN KREDIT DI BANK BRI UNIT BULAKAMBA CABANG BREBES - Ulul Absor (Jurnal Strategik, 2017)
Abstract This study entitled the influence of savings and deposits on lending at the BRI Bulakamba Unit in Brebes Branch. The research method used is collecting data on the amount of savings, deposits, and credit from 2012 to 2016, while the data analysis used is: Multiple regression analysis, coefficient of determination, t test, and test f. From the results of the analysis it can be concluded that: Based on the results of multiple linear regression analysis on Coefficients, the multiple regression model with one Credit dependent variable (Y) with n independent variables the size of Savings (X1) and Deposits (X2) is: Y = - 12,467,949,951,039 + 0,994 (X1) + 0,305 (X2). The constant is -12.467.949,951,039 means that if X1 and X2 value is 0, then profit (Y) value decreases by Rp. 12467949951,039, in the savings constant (X1) of 0.994 Every increase of Rp. 1000 from Savings, Credit will increase by Rp 994, and on the deposit constant (X2) Every increase of Rp. 1000 from a deposit, the credit will increase by Rp. 305. Based on the results of the t test, the Savings magnitude variable (X1) which is 15,898 has a significant effect on Credit because the Savings account is 15,898> of table 4,303, and the variable Deposit (X2) is 1,077, there is no significant effect on credit distribution in the Branch Office BRI Branch Brebes because the tcount of deposits is 1.077